Development of a hybrid behavioural and thermal adaptive building envelope. (December 2019) - Foged, Isak Worre; Pasold, Anke
This study focuses on the design of behavioural mechanisms for a hybrid informed adaptive envelope. Based on a full-scale experimental demonstrator, including a material responsive and a sensor–processing–actuation adaptive system, quantitative and qualitative methods are applied to identify, describe and study behavioural modes of the adaptive envelope. Through sensor data values and observations, the study finds that the adaptive response patterns are best based on subjective, human-mapped sensations, rather than prescribed environmental comfort, numeric-based sensor values. Those adaptive response patterns should account for change in tempi of the environment, occupier and envelope to establish advanced cause and effect relations, beyond generic thermal comfort performance metrics.